Human-Asian wild elephant (Elephas maximus) conflicts and its socio-economic consequences in and around the protected areas of Central Terai, Nepal - Yadav, B. R.; Dutta, C.; Chalise, M. K.; Williams, C. (Banko Janakari, 2015)
The study was carried out in and around the two protected areas of Central Terai, Nepal with the primary aim of assessing the socio economic losses due to human-wild elephant conflicts. The field work was conducted during May 2010 to April 2011 through field observation, household survey, focus group discussion and key informant interviews. Loss of 50 houses and 15 lives were noticed during the study period in the study sites whereas five wild elephants were killed during 2005–2010. An estimated amount of about NRs. 2,000,000 (US$ 25,165) was found as the economic loss due to crop raiding by elephants in Parsa District for the year 2009; whereas it was slightly less to a level of about NRs. 1,600,000 (US$ 20,289) in the year 2010. However, the economic loss due to crop damage by wild elephants raiding in the Buffer Zone (BZ) of the Chitwan National Park (CNP) was nearly half of the Parsa District. The per household economic loss from crop damages were estimated to be around NRs 5,000 (US$ 65.96) and NRS 6,135 (US$ 77.67) in Parsa District and the BZ of the CNP respectively. About 1000 hectares of forestland have been found to be occupied by about 650 families in and around the buffer zone of the CNP and Parsa Wildlife Reserve (PWR). Compensatory relief for victimized families are the immediate solution in reducing the conflict whereas cultivation of unpalatable crops in and around the elephant routes as well as practice of agro-forestry are some of the long term solution in the habitat of wild elephants. Banko Janakari, Vol. 24, No. 1, pp. 47-54